2018
DOI: 10.1155/2018/8474617
|View full text |Cite
|
Sign up to set email alerts
|

Th1/Th2 Dichotomy in Obese Women with Gestational Diabetes and Their Macrosomic Babies

Abstract: The aim of the study was to assess T cell differentiation and the modulation of inflammatory cytokines in obese and gestational diabetes mellitus (GDM) women and their macrosomic newborns. Hence, immediately after delivery, blood samples were collected through the mother's arm vein and the umbilical cordon vein. Biochemical parameters measured were HbA1C, glucose, insulin, triglyceride (TG), total cholesterol (Tchol), HDL cholesterol (HDLchol), and LDL cholesterol (LDLchol). T lymphocytes were purified from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 37 publications
3
10
0
Order By: Relevance
“…High production of IFN-γ and low level of IL-4 confirmed the proinflammatory Th1 phenotype in insulin-treated T2D pregnant women as well as in women with GDM in this study. Our results are in agreement with those of Seck et al [4] who reported the proinflammatory status in pregnant diabetic women, which could be responsible of recurrent miscarriage and spontaneous abortion [3].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…High production of IFN-γ and low level of IL-4 confirmed the proinflammatory Th1 phenotype in insulin-treated T2D pregnant women as well as in women with GDM in this study. Our results are in agreement with those of Seck et al [4] who reported the proinflammatory status in pregnant diabetic women, which could be responsible of recurrent miscarriage and spontaneous abortion [3].…”
Section: Discussionsupporting
confidence: 94%
“…Several studies have gained interest into the immunopathology and physiopathology of gestational diabetes mellitus (GDM), type 1 or type 2 diabetic pregnancy [1][2][3][4]. However, few is known about the implication of immune cells in pregnancy complicated by diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…Since the blood of the fetus and the mother are shared, while the high concentrations of insulin in the mother exerted its metabolic effects on her own physiology, the development of acanthosis nigricans indicates a high degree of insulin resistance and a concomitant excess of circulating compounds such as glucose, amino acids, free fatty acids and others in the mother’s blood 29. Hence, the growing fetus was definitely exposed via the placenta to a larger load of circulating nutrients present in the mother’s circulation, event that should have led to fetal hyperinsulinaemia 30. Under such circumstance, rather than functioning as a metabolic hormone, fetal insulin might have acted as a growth factor in the fetus using various binding sites, including the insulin, IGF-I and hybrid insulin/IGF-I receptors.…”
Section: Case Discussionmentioning
confidence: 99%
“…It is the most common metabolic disease during pregnancy and its incidence is increasing worldwide [4,5]. As we have recently reported, GDM is one of the major endocrine abnormalities that can induce disruption of several biochemical and immunological parameters [3,[6][7]. Recently, there has been renewed interest in immunological parameters including immune cell subpopulations and cytokines which are designated as predictors of endothelial dysfunction and inflammation [8].…”
Section: Introductionmentioning
confidence: 99%
“…Sedentary and modern lifestyle in developing countries contribute to the increased prevalence of GDM [23,24]. Early diagnosis of gestational diabetes, based on biochemical and immunological parameters, could be crucial to anticipate the care of pregnant diabetic women and thus prevent the wide range of adverse consequences on the offspring, including macrosomia, fetal death, prematurity, birth trauma, respiratory distress syndrome, obesity, impaired glucose tolerance, and type 2 diabetes in adulthood [7,12,25].…”
Section: Introductionmentioning
confidence: 99%